2016
DOI: 10.1097/meg.0000000000000581
|View full text |Cite
|
Sign up to set email alerts
|

Persisting changes of intestinal microbiota after bowel lavage and colonoscopy

Abstract: We provide clear evidence that, in normal individuals, a high-volume polyethylene glycol bowel cleansing preparation has a long-lasting effect on the gut microbiota composition and homeostasis, in particular, with a decrease in the Lactobacillaceae abundance, a population of protective bacteria. Further studies are required to assess whether these changes have any metabolic, immunological, or clinical consequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
93
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(98 citation statements)
references
References 33 publications
2
93
1
2
Order By: Relevance
“…Jalanka et al [33] demonstrated a decrease in the abundance of the members of Clostridium cluster IV and increased the members of Clostridium cluster XIVa and Proteobacteria. Other studies identifying changes caused by bowel cleansing include Harrell et al [30], O’Brien et al [32], Mai et al [34], Drago et al [35] and Jain et al [36], whilst other studies have failed to demonstrate changes [37–39]. The findings of the current study are most relevant to the type of bowel preparation that we used, i.e.…”
Section: Discussionmentioning
confidence: 62%
“…Jalanka et al [33] demonstrated a decrease in the abundance of the members of Clostridium cluster IV and increased the members of Clostridium cluster XIVa and Proteobacteria. Other studies identifying changes caused by bowel cleansing include Harrell et al [30], O’Brien et al [32], Mai et al [34], Drago et al [35] and Jain et al [36], whilst other studies have failed to demonstrate changes [37–39]. The findings of the current study are most relevant to the type of bowel preparation that we used, i.e.…”
Section: Discussionmentioning
confidence: 62%
“…In the same manner, a very recently published paper further underlines that, immediately after bowel lavage, a significant reduction in Lactobacillaceae and an increase in Enterobacteriaceae abundance were prominent; 30 days later these families were still significantly lower, while Streptococcaceae had increased 4-fold compared with samples collected before lavage [23]. …”
Section: Intestinal Microbiota: Symbiosis and Dysbiosismentioning
confidence: 99%
“…Aroniadis 2018 gastrointestinal route of administration, reported that they used bowel lavage as part of their FMT protocol. [30][31][32] There is evidence to suggest that bowel lavage itself can alter the faecal microbiota in healthy individuals, 41,42 although whether this in itself has any effect on symptoms in people with IBS is uncertain.…”
Section: Control Intervention (Number Of Patients)mentioning
confidence: 99%